Article Review “Nanotechnology and Carbon Nanotubes: Definition, Properties” (Journal of University of Babylon for Engineering Sciences, 2021)
Nowadays it is difficult to imagine life without nano-technologies, more specific: nanomaterials. Carbon nanotubes are of the most famous important materials used in this field. (CNTs) are allotropes of carbon element, which made of graphite, constructed in a cylindered tube its dimension are nanometers in diameter while reach to a millimetre in length. there unique structural, electronic, mechanical properties are due to high aspect ratio nanoparticles (HARN). many industrial methods are used to produce (CNTs), (CVD) is the most famous method, it is a simple technique with low-cost respect to others. Laser ablation and arc discharge are also used. Foreign nanoparticles (during synthetic technologies) and structural defects are the most major problems associated with (CNTs) manufacturing which lead to a degradation in properties so that purification is needed to enhance reactivity and homogenous structure.